Pengaruh Konsumsi Air Kelapa Hijau Terhadap Penurunan Nyeri Disminorhea Pada Siswi Di SMA PAB 6 Helvetia Medan Tahun 2022 - Marlina, Marlina; Pratiwi , Debby; Mouliza, Nurul (Journal of Pharmaceutical and Sciences, 2024)
The problem of menstrual pain is the problem most often complained of when women come to the doctor regarding menstruation. Menstrual pain can attack women who menstruate at any age. There is no age limit, and it is often accompanied by aggravating conditions such as dizziness, cold sweats, and even fainting. The research aimed to determine how giving young green coconut water reduces dysmenorrhea pain in adolescents. This research method uses a pre-experimental design using a one-group pre-test post-test approach. The research population was 40 people, and a quota sampling technique was used. The population in this study was young people, and the sample size was 17 respondents. Based on the results of statistical tests using the Wilcoxon test, the Asymp.The sig (2-tailed) value was 0.00; this value is smaller than the alpha (α) value of 0.05. so it can be concluded that Ha is accepted and Ho is rejected, so it can be concluded that there is a significant effect before and after being given a drink of young green coconut water on reducing dysmenorrhea pain. The results of this study concluded that young green coconut water had a significant effect on lowering dysmenorrhea pain.